The role of genetic research with family design in the study of affective disorders - E. D. Kasyanov; G. E. Maso; A. O. Kibitov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2019)
Affective disorders (recurrent depressive disorder and bipolar affective disorder) are multifactorial and polygenic diseases, which suggests the involvement of multiple neurobiological mechanisms. The phenotype of affective disorders is a heterogeneous group of clinically similar psychopathological symptoms, which also makes it difficult to detect potential biomarkers and new therapeutic targets. To study families at high risk of developing affective disorders using both clinical and molecular genetic approaches can help to study the neurobiological basis of depressive conditions, as well as to identify endophenotypes of affective disorders. The most important criterion for an endophenotype is its heritability, which can be proved only within the framework of the family design of the study. Comprehensive clinical and molecular genetic studies based on family design have the best prospects.